PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE CIRC DAN KEBIASAAN MEMBACA TERHADAP KETERAMPILAN MENULIS TEKS CERPEN - Refril Dani; Ikhsan Maulana Putra; Aprizan Aprizan (LP3M Universitas Muhammadiyah Muara Bungo, 2022)
This research aims to see the effect of the cooperative learning model type Cooperative Integrated Reading and Competition which is then written with the abbreviation CIRC, and to see the effect of high appreciative reading habits and low on the student's skills of writing a short story at class XI SMA Negeri 1 Ampek Angkek Agam. This type of research is quantitative, The method used in this research is the experimental method. research From the results of the research conducted can be concluded four things as follows. First, the skill in writing short stories of students taught by using the CIRC-type cooperative learning model is better than the students taught using the conventional learning model. Second, the skill in writing short stories of students who have highly appreciative reading habits taught by using the CIRC type cooperative learning model is better than those taught by using the conventional learning model. Third, the skill in writing short stories of students who have low appreciative reading habits taught by using the CIRC type cooperative learning model is better than those taught by using the conventional learning model. Fourth, there is no interaction between appreciative reading habits and the CIRC cooperative learning model in influencing the student's skills in writing a short story.